KEHIDUPAN SUFISTIK PADA PONDOK PESANTREN BIBAḤRI ‘ASFARAḤ SANANREJO, TUREN, MALANG - Musthofa Musthofa (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2015)
Abstract: The article will explore the sufi’s life at the Islamic boarding school (pesantren) Bibaḥri ‘Asfarah Sanarejo, Turen, Malang. The focus of study is the practies and how they practice to become a sufi, how their circumstance of mind when practicing, and how their circumstance of mind after practicing. The santri who never studying at the Pesantren can be divided three categories: al-Fussāq, al-Fusyl, and al-Abriyā’. The method used to a sufi’s life are mapped in two kinds of practices namely inward (bāṭiniya) and outward (lahiriya) practices. The inward practices include ṣalawat (prayer for the Prophet Muhammad pbuh), istighāṡah (mass prayer), asmā’ al-ḥusnā (reciting name of God), Yāsīn recital. The outward practices include spiritual traveling, cleaning the pesantren environment, installing paving and ornaments, making bricks, taking care of animal, becoming a sectary and treasures of the pesantren. Those inward practices are called riyāḍah (the spiritual excercise). The soul circumstances (aḥwāl) while performing those practices could be described that they feel muḥāsabah (introspective), wuṣūl (pure), happy, excited, khauf (fearful), and rajā’ (hopeful). Asbtrak: Artikel ini akan memaparkan kehidupan sufistik di Pondok Pesantren Bibaḥri ‘Asfarah Sanarejo, Turen, Malang. Fokus bahasan adalah amalan-amalan dan tata cara para santri dalam mengamalkan ajaran tasawuf sehingga mereka layak disebut sufi, keadaan jiwa selama dan setelah mereka mengamal ajaran tasawuf. Santri yang belum mondok dibagi dalam tiga kelompok: al-Fussāq, al-Fusyl, dan al-Abriyā’. Jalan yang santri tempuh menuju kehidupan sebagai sufi, antara lain, melalui pengamalan-pengamalan yang dipetakan menjadi dua jenis: pengamalan bersifat lahiriah dan batiniah. Yang termasuk pengamalan batiniah adalah pengamalan ṣalawat, istighāṡah, asmā’ al-ḥusnā, membaca surat Yāsīn; sedangkan pengamalan lahiriahnya adalah musafir, membersihkan lingkungan pondok, memasang paving dan ornament, mencetak bata, memelihara binatang, sekretaris, dan bendahara pondok. Pengamalan lahiriah ini disebut riyāḍah. Keadaan-keadaan jiwa mereka (aḥwāl) mengamalkan ajaran tasawuf akan merasakan pengalaman-pengalaman spiritual (spiritual experience) seperti muḥāsabah, wuṣūl, senang, gembira, khauf, dan rajā’. Di lain pihak, para santri yang telah mengamalkan ajaran tasawuf tersebut akan mengalami perubahan yang baru seperti merasa senang, gembira, beriman, ṣaddiq, tenteram, wuṣūl, yakin, tawaḍu’, zuhud, dan ikhlas. Keywords: al-Fussāq, al-Fusyl, al-Abriyā’, tasawuf, dan sufi.